The “four footed” Lepanthes (Pleurothallidinae), a new species from north-western Ecuador - Baquero, Luis E.; Moreno, Juan Sebastián; Iturralde, Gabriel Alfredo (Lankesteriana: International Journal on Orchidology, 2018)
A new species of Lepanthes, closely resembling L. hexapus and L. aguirrei, is described and illustrated. The new species is characterized by bilobed, filiform and curved petals. Ecological and taxonomic notes are given. In addition, the first known locality for L. bibarbullata is presented herein.